Dentoalveolar Effects Following Maxillary Expansion: Comparison Between Dental and Skeletal Anchorage - Francesca Cremonini; Patrizia Pieralli; Paolo Albertini; Mario Palone (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare the dento-alveolar effects between dental and skeletal anchored expansion devices to achieve maxillary expansion in different groups of patients: pure dental anchorage was used in growing patients and skeletal anchorage in adult patients. Linear, angular and volumetric parameters have been analysed. Material and Methods: 22 patients has been selected from the total archive of patients treated in the Orthodontics Department of the University of Ferrara, Italy, divided into 3 groups according to the appliance used to obtain the transversal maxillary correction. Digital files of the upper arch were obtained from scans performed using an intro-oral scanner before treatment (T0) and at the end of expansion (T1). Therefore, linear, angular and volumetric measurements have been performed. Results: There is a highly significant statistic variation of the 3-3, 4-4 and 6-6 diameter as a function of time. There was a statistically significant variation of the palatal vault angle and of the 6-6 distance at the cusp level as a function of time. Moreover, it appears that these parameters are reduced in the group with skeletal anchored expander. No tooth considered have encountered a statistically significant change in tip and torque values, no matter the type of RPE and the treatment time. For all patients, we have recorded the superimposition of the maxillary dental cast before and after treatment. Conclusion: In all patients, we obtained a resolution of the maxillary transverse deficit. Patients treated by pure skeletal anchored devices have recorded a less variations of palatal vault angle and the distance between first molar cusps, as if the expansion was gained more parallel. The expansion obtained showed reduced dental side effects, as tip and torque values haven't changed in a statistically significant way.